Gamified digital media: Innovative media for strengthening first grade elementary students' writing literacy - Cerianing Putri Pratiwi; Heny Kusuma Widyaningrum; Nico Irawan (BAHASTRA, 2026)
This study aimed to develop gamification-based digital media as an innovative learning tool to strengthen the writing literacy of first-grade elementary school students. The research used a Research and Development (R&D) method with the ADDIE model. Data were collected through expert validation questionnaires, teacher and student evaluation questionnaires, and writing skills tests. The results showed that the developed media had a high feasibility level, with material expert validation scores of 81.7 (very feasible) and media expert scores of 80.2 (feasible). User evaluations also showed very positive responses, with average scores of 82.0 from teachers and 82.75 from students. The effectiveness test results indicated that students who learned using gamification-based digital media had an average writing literacy ability of 85.71, higher than the conventional learning group at 77.50, with a statistically significant difference (t = 3.867; p < 0.001). This finding shows that integrating gamification elements can boost student engagement while also supporting the development of early writing skills through a more interactive, gradual, and motivating learning experience. This study offers theoretical contributions to the development of gamification-based literacy learning, pedagogical contributions as an alternative, more innovative writing teaching strategy, and practical contributions by providing effective digital media to support the enhancement of elementary students' writing literacy.